Effect of the US-Mexico border region in cardiovascular mortality: ecological time trend analysis of Mexican border and non-border municipalities from 1998 to 2012 - Gabriel Anaya; Wael K Al-Delaimy (BMC, 2017)
Abstract Background An array of risk factors has been associated with cardiovascular diseases, and developing nations are becoming disproportionately affected by such diseases. Cardiovascular diseases have been reported to be highly prevalent in the Mexican population, but local mortality data is poor. The Mexican side of the US-Mexico border has a culture that is closely related to a developed nation and therefore may share the same risk factors of cardiovascular diseases. We wanted to explore if there was higher cardiovascular mortality in the border region of Mexico compared to the rest of the nation. Methods We conducted a population based cross-sectional time series analysis to estimate the effects of education, insurance and municipal size in Mexican border (n = 38) and non-border municipalities (n = 2360) and its association with cardiovascular age-adjusted mortality rates between the years 1998-2012. We used a mixed effect linear model with random effect estimation and repeated measurements to compare the main outcome variable (mortality rate), the covariates (education, insurance and population size) and the geographic delimiter (border/non-border). Results Mortality due to cardiovascular disease was consistently higher in the municipalities along the US-Mexico border, showing a difference of 78 · 5 (95% CI 58 · 7-98 · 3, p < 0 · 001) more cardiovascular deaths after adjusting for covariates. Larger municipal size and higher education levels showed a reduction in cardiovascular mortality of 12 · 6 (95% CI 11 · 4-13 · 8, p < 0 · 001) deaths and 8 · 6 (95% CI 5 · 5-11 · 8, p < 0 · 001) deaths respectively. Insurance coverage showed an increase in cardiovascular mortality of 3 · 6 (95% CI 3 · 1-4 · 0, p < 0 · 001) deaths per decile point increase. There was an increase in cardiovascular mortality of 0 · 3 (95% CI −0 · 001-0 · 6, p = 0 · 050) deaths per year increase in the non-border but a yearly reduction of 2 · 9 (95% CI 0 · 75-5.0, p = 0 · 008) deaths in the border over the time period of 1998-2012. Conclusion We observed that the Mexican side of the US-Mexico border region is disproportionately affected by cardiovascular disease mortality as compared to the non-border region of Mexico. This was not explained by education, population density, or insurance coverage. Proximity to the US culture and related diet and habits can be explanations of the increasing mortality trend.